The efficiency of polymotivation in studying Russian as a foreign language in the course of intensive preparation for admission to a university - Nuriet Kadyrbechevna Bolokova (Вестник Майкопского государственного технологического университета)
The article is devoted to the urgent problem of modern education - increasing the motivation of students, the influence of various motivational components on the effectiveness of intensive study of a foreign language in the framework of pre-university training, which implies the study of complex grammatical and lexical material in a short time period and requires increased motivation from students. The relevance of the research is due to the importance of a thorough scientific study of the influence of students’ motivation on learning outcomes and the study of methods and techniques for increasing both motivation and the successful implementation of the anthropocentric, communicative-cognitive and personality-oriented paradigm of teaching Russian as a foreign language (Russian as a foreign language). The purpose of the study can be defined as the systematization of existing pedagogical techniques to increase the motivation of students and the search for new ones, as well as the analysis of factors that reduce the motivation of students. The main research method is scientific analysis, observation and generalization. The key results of the research are the introduction of the term "polymotivation", its definition and role in the teaching process; presentation of the experience of increasing polymotivation among foreign students undergoing training at the preparatory department. It has been concluded that motivation, when divided into external and internal, cannot be considered and applied separately, as a self-sufficient unit; the term "polymotivation" is introduced as a sublimation of the types of motivation used in the teaching process; the methods and techniques of increasing polymotivation in the classroom in Russian as a foreign language have been analyzed.